2004
DOI: 10.1007/s00277-004-0877-4
|View full text |Cite
|
Sign up to set email alerts
|

Philadelphia (Ph) chromosome-positive thrombocythemia without features of chronic myeloid leukemia in peripheral blood: natural history and diagnostic differentiation from Ph-negative essential thrombocythemia

Abstract: We have evaluated the clinical symptoms, hematological features, and natural history of 3 cases and 20 reported cases described as Philadelphia chromosome-positive (Ph+) essential thrombocythemia (ET). The presence of increased small mononuclear megakaryocytes in bone marrow smears and biopsy material in patients with pronounced thrombocytosis and no evidence of chronic myeloid leukemia (CML) in peripheral blood appeared to be a diagnostic clue to the diagnosis of Ph+ (essential) thrombocythemia. As compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…A recent large international study confirmed the prognostic relevance of distinguishing ET from pre-fibrotic PMF [26]. In the absence of JAK2/CALR/MPL mutations, the possibility of chronic myeloid leukemia (CML) is readily addressed by BCR-ABL1 mutation screening, but it is also to be noted that megakaryocytes in CML (small and hypolobulated) are easily distinguished from those of ET [46] The diagnosis of post-PV or post-ET MF should adhere to criteria recently published by the International Working Group for MPN Research and Treatment (IWG-MRT) (Table III) [47]. …”
Section: Diagnosismentioning
confidence: 99%
“…A recent large international study confirmed the prognostic relevance of distinguishing ET from pre-fibrotic PMF [26]. In the absence of JAK2/CALR/MPL mutations, the possibility of chronic myeloid leukemia (CML) is readily addressed by BCR-ABL1 mutation screening, but it is also to be noted that megakaryocytes in CML (small and hypolobulated) are easily distinguished from those of ET [46] The diagnosis of post-PV or post-ET MF should adhere to criteria recently published by the International Working Group for MPN Research and Treatment (IWG-MRT) (Table III) [47]. …”
Section: Diagnosismentioning
confidence: 99%
“…47 Finally, it has been proposed that cytogenetic analysis should be undertaken in all cases of ET, as rarely CML may present with an identical phenotype. [48][49][50] Although such presentations are rare, the success of tyrosine kinase inhibitors in CML makes it important that such a diagnosis is not missed. 51 Finally, cytogenetic analysis of haematopoietic colonies suggests that, at least in some patients, the disease can arise at the multipotent stem cell level.…”
Section: Essential Thrombocythaemiamentioning
confidence: 99%
“…The clinical outcome of BCR/ABL positive ET is poor as compared to BRC/ABL-negative thrombocythemia in MPD [14]. The bone marrow in BCR/ABL positive ET is featured by predominant and pronounced mononucleated megakaryopoiesis with initial no, minor or overt granulocytic hypertrophy consistent with CML.MP (Figure 1).…”
Section: Ph-positive Essential Thrombocyhemia (Et)mentioning
confidence: 99%
“…The bone marrow in BCR/ABL positive ET is featured by predominant and pronounced mononucleated megakaryopoiesis with initial no, minor or overt granulocytic hypertrophy consistent with CML.MP (Figure 1). Important differences between BCR/ABLpositive ET and BCR/ABL-positive CML at time of presentation are the predilection of BCR/ABL-positive ET for females and the absence of splenomegaly [14]. Ph-positive ET patients have no features of CML in the peripheral blood at time of presentation.…”
Section: Ph-positive Essential Thrombocyhemia (Et)mentioning
confidence: 99%
See 1 more Smart Citation